Investigating the Impact of Research-Based Learning on Conceptual Understanding in Thermal Conduction - Gunarjo Suryanto Budi; Theo Jhoni Hartanto; Fenno Farcis; Elis Triwati; Muhammad Fajar Ma’ruf (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the impact of research-based learning on students’ conceptual understanding of thermal conduction. The research employed a one-group pretest-posttest design involving 20 pre-service physics teachers enrolled in a thermodynamics course. The research instrument used was a conceptual understanding test administered before and after implementing research-based learning. The Shapiro-Wilk normality test indicated that both pre-test and post-test data were normally distributed (p > 0.05). A paired samples t-test revealed a significant difference between pre-test and post-test scores (Sig. (2-tailed) = 0.000 < 0.05), suggesting that research-based learning effectively enhanced students’ conceptual understanding. Furthermore, the N-Gain analysis resulted in a score of 0.71, categorized as high, indicating a substantial improvement in students’ conceptual mastery. These findings suggest that research-based learning is an effective instructional approach in teaching thermal conduction, fostering deeper conceptual comprehension among students.